Juridical Analysis of the Concept of “Legislation” in the New Criminal Code: Implications and Applications - Melvin Elvino Putra; Lukman Dwi Atmaja (JUSTITIA JURNAL HUKUM, 2024)
The phrase "statutory regulations" in Article 1 paragraph (1) of Law Number 1 of 2023 concerning the Criminal Code (KUHP) contains the meaning that criminal provisions can be regulated by various hierarchies of statutory regulations, as regulated in Law Number 12 of 2011 concerning the Formation of Legislation. However, this is contrary to the basic principle of the formation of criminal provisions, namely the principle of nullum crimen sine lege parliamentaria, which means that the formulation of criminal sanction norms can only be determined if it has obtained the approval of the people, through their representatives in the People's Representative Council (DPR) for the level of laws and the approval of the governor, regent, or mayor for regional regulations. This study uses a normative legal research method with a statutory approach. The results of the study show that Article 1 paragraph (1) of Law Number 1 of 2023 contains unclear norms, because the phrase "statutory regulations" opens up the possibility that criminal provisions can be made by parties other than people's representatives, which can obscure the principle of representation in the formation of criminal provisions